초등학교 수학에서 수직과 평행의 지도 방안 탐색 - 김정원 (한국초등수학교육학회지, 23(4), 2019)
수학의 기본 개념인 수직과 평행은 현행 2015 개정 교육과정에 따른 교과서에서 이전 2009 개정 교육과정에 따른 교과서에 비하여 축소되어 제시된다. 본 연구에서는 초등학교 수학에서 수직과 평행 개념의 지도 방안을 탐색하기 위하여 한국의 2009 개정 및 2015 개정 초등학교 수학과 교육과정 및 그에 따른 교과서에서 수직과 평행에 관한 내용을 분석하고, 한국과 싱가포르, 일본 교과서에서 수직과 평행 개념의 지도 방법을 비교 분석하였다. 교과서 분석을 바탕으로 4학년 2학기 4. 사각형 단원에서 다루어지는 수직과 평행 수업을 재구성하여 실행하였다. 교과서 분석 결과, 2009 개정 교육과정에 따른 교과서에서 2015 개정 교육과정에 따른 교과서로 변화할 때 단원명 및 차시 구성의 차이가 있었으며, 한국과 싱가포르, 일본 교과서는 수직과 평행의 개념 정의 및 활동 내용에서 차이를 드러냈다. 수업의 계획 및 실행에서는 수직과 평행 개념의 의미를 이해하고, 수선 및 평행선 긋는 방법을 탐색하며, 실생활과의 연관성에 초점을 두었다. 본 연구 결과를 통하여 초등학교 수학에서 수직과 평행을 의미 있게 지도할 수 있기를 기대한다. Perpendicularity and parallelity are important concepts in Mathematics as well as real-life contexts. However, those concepts are rather reduced in 2015 revised curriculum compared to previous 2009 revised curriculum. This study firstly analyzed teaching method related to perpendicularity and parallelity in a series of mathematics textbooks of Korea, Singapore and Japan. Moreover, the unit of perpendicularity and parallel was redesigned in a way to understand the concepts meaningfully and to give opportunities for students to explore how to make perpendicular and parallel lines. The results showed that noticeable changes has been as the curriculum was revised in Korea. Also, three countries showed some differences in concepts definition and learning activities. This study is expected to suggest implications for how to teach perpendicularity and parallelity in elementary school mathematics. KCI Citation Count: 0